Regional Administration Management: Village Boundaries Averment in Sangihe Islands Regency - Bataha, Katerina; Monintja, Donald K.; Anisykurlillah, Rosyidatuzzahro (Universitas Muhammadiyah Gorontalo, 2024)
The purpose of the Minister of Home Affairs regulations Number 45 of 2016 is to create an orderly village government administration, provide clarity and legal certainty on village boundaries that meet technical and juridical aspects. Data shows that regional administration management, especially the affirmation of village boundaries in Indonesia, is still not optimal, where only 1,479 villages out of 74,962 villages have determined village boundaries. North Sulawesi Province, which consists of 1,507 villages, so far, only the Sangihe Regency Government has drafted 6 regional regulations related to the affirmation of village boundaries. The unclarity of village boundaries will automatically affect village development planning and the amount of village fund budget because the amount of village funds is adjusted and divided based on population, area, poverty rate, and geographical difficulty. With this condition, there are indications that the determination of the amount of village funds that are the government's flagship program is currently implemented not following valid village boundary rules and data. This research uses qualitative methods with a case study approach to explain the management of regional administration, especially boundary affirmation carried out in Sangihe Islands Regency, and factors that influence the implementation of village boundary affirmation